Risk of hospitalisation after early-revisit in the emergency department. - Cozzi, Giorgio; Ghirardo, Sergio; Fiorese, Ilaria; Proietti, Ilaria; Monasta, Lorenzo; Minute, Marta; Barbi, Egidio; Calligaris, Lorenzo (J Paediatr Child Health, 2017)
AIM: Early-revisits are frequent in the paediatric emergency department (ED) setting, but few data are available about early-revisited patients. The aim of this study was to investigate the hospitalisation rate of a population of early-revisited patients and to detect if an early-revisited patient was at risk of a more severe disease. METHODS: Between June 2014 and January 2015, we conducted a retrospective cohort study, considering all patients presented to the ED of a tertiary level children's hospital in Italy. We selected all patients who were revisited within 72 h from the initial visit (study cohort), while all other patients accessed in the same period were considered the control cohort. The two cohorts were compared for age, gender, triage category, hospitalisation rate, diagnosis at admission and hospital length of stay. RESULTS: In the study period, we reviewed 10 750 visits, of which 430 (4%) were unplanned revisits for the same chief complaint within 72 h from the initial visit. Hospitalisation rate of early-revisited patients was significantly higher compared to control patients (8.4 vs. 2.9%). Hospitalisation rate increases in parallel with the number of revisits, but in many cases, it was not directly related to a worst triage category, neither to a longer hospital length of stay. CONCLUSION: Early revisited patients in the ED had a significantly higher risk of hospitalisation, but this risk was only partially related to their clinical conditions.
Keywords: Adolescent; Child; Child, Preschool; Emergency Service, Hospital; Female; Hospitalization; Humans; Infant; Italy; Male; Retrospective Studies; Risk Assessment; Tertiary Care Centers; Time Factors